Synthesis of N,N-diethylaminopropylurea and Monosubstituted Urea Derivatives from Primary Amines and Potassium Cyanate - Chang, Wei-Jin; Liew, Sook Yee; Tan, Siow-Ping (Letters in Organic Chemistry, 2023)
Urea derivatives are an important class of pharmacologically-active compounds due to their ability to form hydrogen bonds with biological targets. Several synthetic pathways have been developed to access urea derivatives, such as the metal-free and metal-catalysed carbonylation reactions of amines and the Curtius, Hofmann, and Tiemann rearrangement reactions. This study aimed to synthesize urea derivatives from primary amines. The urea derivatives were synthesized from primary amines and potassium cyanate in 1M HCl aqueous solution under ambient conditions and were isolated, followed by characterization using FTIR, DSC, and NMR (1H and 13C). A new urea derivative, N, N-diethylaminopropylurea (6), together with N-phenylurea (1), para-tolylurea (2), orthomethoxyphenylurea (3), para-methoxyphenylurea (4), N-benzylurea (5), and N-butylurea (7), was successfully synthesized under acidic conditions. This work presents the synthesis and characterization data of a newly-reported urea derivative, N, N-diethylaminopropylurea (6), and extends the substrate scope to basic side chains in the synthesis of urea derivatives from primary amines and potassium cyanate in water.
Keywords: N-benzylurea